`Society thinks they are cold and/or incompetent, but I do not': Stereotype content ratings depend on instructions and the social group's location in the stereotype content space - Patrick F. Kotzur; Susanne Veit; Annika Namyslo; Mirka-Alicia Holthausen; Ulrich Wagner; Ruta Yemane (British Journal of Social Psychology, 2020)
Stereotype content researchers have grown accustomed to ask participants how `society' views social groups to tap into culturally shared stereotype content and to reduce social desirability bias (J Person Soc Psychol, 82, 2002, 878). However, methodological and theoretical considerations raise questions about this common practice, and stereotype content researchers have also asked for participants' personal perspective on social groups in the past. Nonetheless, how and whether stereotype content model scores empirically differ as a function of the instructed perspective remains questionable and to date untested. Thus, we investigated whether and, if so, how stereotype content results are affected when instructing participants to evaluate social groups from society's versus their personal perspective. Across three experiments (Study 1: N = 301; Study 2: N = 126; Study 3: N = 1,221), latent mean comparisons indicated that results regarding stereotype content ratings are affected by the instructed perspective (society's vs. personal) contingent on the social group's location in the stereotype content space: Stereotype content ratings were more negative when participants were asked to provide society's perspective on social groups compared to their own perspective, but only on an already depreciated stereotype content dimension. The number of possible comparisons across experimental conditions was substantially reduced, since preconditions for these analyses were not met. Given our methodological and theoretical considerations and empirical corroborations that the instructed perspective does affect results, we encourage a discussion on how to best measure culturally shared stereotype content and propose aggregating stereotype content scores from participants' personal perspective to the cultural level.
Keywords: 300; stereotype content model; social cognition; instructions; perspective; latent variable modelling